Diversity and biogeography of Ni‐hyperaccumulators of Alyssum section Odontarrhena (Brassicaceae) in the central western Mediterranean: evidence from karyology, morphology and DNA sequence data. (3rd September 2013) - Cecchi, Lorenzo; Colzi, Ilaria; Coppi, Andrea; Gonnelli, Cristina; Selvi, Federico
Abstract : The diversity of Alyssum section Odontarrhena in the central–western Mediterranean region was investigated to elucidate relationships and biogeography of Ni‐hyperaccumulators in the group. Karyological, morphometric and molecular phylogenetic analyses were performed on accessions of Ni‐hyperaccumulators from serpentine outcrops and non‐hyperaccumulators from calcareous–dolomitic soils in the region. Alpine and Apennine populations of A. argenteum, Sardinian A. tavolarae and some Tuscan A. bertolonii had a tetraploid chromosome complement and larger silicles, seeds and seed wings than diploid accessions. DNA sequences from the plastid rpoC1 locus corroborated the monophyly of section Odontarrhena but species relationships were poorly resolved. Bayesian analysis of combined ITS‐ rpoC1 sequences retrieved three main lineages including hyperaccumulators and non‐hyperaccumulators of contrasting geographical origin. One lineage was mainly continental and included alpine and northern Apennine populations of A. argenteum, the Balkan complex of A. murale and the Iberian group of A. serpyllifolium, sister to Corsican A. robertianum as suggested by their similar diploid karyotype. In this clade no divergence was found between typical A. serpyllifolium and related Ni‐hyperaccumulator races from the Iberian peninsula, supporting their conspecific status. A second lineage was prevalently Mediterranean and included the sister species A. bertolonii and A. tavolarae, and other endemics from Sicily, the southern Balkans and Turkey from dolomite and serpentine habitats. The present data suggest new model systems consisting of hyperaccumulators and non‐hyperaccumulators of proven phylogenetic affinity for further research on the molecular mechanisms of Ni‐hyperaccumulation and serpentine tolerance at the diploid and tetraploid level. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 173, 269–289.